Physicochemical characteristic of neodymium oxide-based catalyst for in-situ CO2/H2 methanation reaction - Salmiah, Jamal Mat Rosid; Susilawati, Toemen; Wan Azelee, Wan Abu Bakar; Zamani, A. H.; Wan Nur Aini, Wan Mokhtar (Elsevier Ltd., 2019)
Carbon dioxide emission to the atmosphere is worsened as all the industries emit greenhouse gases (GHGs) to the atmosphere, particularly from refinery industries. The catalytic chemical conversion through methanation reaction is the most promising technology to convert this harmful CO2 gas to wealth CH4 gas for the combustion. Thus, supported neodymium oxide based catalyst doped with manganese and ruthenium was prepared via wet impregnation route. The screening was initiated with a series of Nd/Al2O3 catalysts calcined at 400 °C followed by optimization with respect to calcination temperatures, based ratios loading and various Ru loading. The Ru/Mn/Nd (5:20:75)/Al2O3 calcined at 1000 °C was the potential catalyst, attaining a complete CO2 conversion and forming 40% of CH4 at 400 °C reaction temperature. XRD results revealed an amorphous phase with the occurrence of active species of RuO2, MnO2, and Nd2O3, and the mass ratio of Mn was the highest among other active species as confirmed by EDX. The ESR resulted in the paramagnetic of Nd3+ at the g value of 2.348. Meanwhile nitrogen adsorption (NA) analysis showed the Type IV isotherm which exhibited the mesoporous structure with H3 hysteresis of slit shape pores.